Politik Hukum Penataan Formasi Jabatan Notaris ditinjau dari Undang-undang Jabatan Notaris - Grisda Lediyoung Lay (Journal of Mandalika Literature, 2024)
Legal politics can occur without us realizing it, one of the polemics is legal politics in carrying out the position of notary where in an area where there are many opportunities to carry out the position there is greater because it has a dense population and has high economic value, so it can give rise to competition. Therefore, there is a phenomenon of sharing space and providing space for those who need it or what is known as a serviced office. Apart from the problems regarding the increasingly dense population and the uneven distribution of notary position formations, there is also another phenomenon where notaries have office addresses that are different from their PPAT addresses, which raises the question of why this difference in address can be approved in carrying out the position of notary. This research uses normative analysis with results where the phenomenon of using a serviced office in carrying out the position of notary is certainly contrary to Article 22 of Law Number 2 of 2014 concerning Amendments to Law Number 30 of 2004 concerning the Position of Notary and Article 3 paragraph 8 of the Notary's Code of Ethics. . Apart from that, there are different notary offices with different PPAT addresses which of course contradicts Article 17 paragraph 1 letter (g) and 19 paragraph 2 UUJN. Then, legal action against the existence of legal politics structuring the formation of notary positions is by issuing Regulation of the Minister of Law and Human Rights Number 62 of 2016 concerning Amendments to Regulation of the Minister of Law and Human Rights Number 25 of 2014 concerning Requirements and Procedures for Appointment, Transfer, Dismissal and Extension of the Notary's Term of Office then Regulation of the Minister of Law and Human Rights Number 36 of 2015 concerning Amendments to Regulation of the Minister of Law and Human Rights Number 26 of 2014 concerning the Formation of Notary Positions which explains in detail the distribution of Notaries and their areas of office.